PENGARUH KINERJA KEUANGAN TERHADAP HARGA SAHAM PADA PERUSAHAAN MANUFAKTUR TERDAFTAR DI BURSA EFEK INDONESIA - Titi, Palentina; Ulfah, Maria; Rosyid, Rum (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis study is an attempt to find out the effect of financial performance (profitability and leverage) on stock prices in the registered Manufacturing companies in Indonesia Stock  Exchange. The research methodology used was descriptive. The data used in this research was annual financial reports and close stock prices (closing prices)of 36 registered Manufacturing companies in Indonesia Stock Exchange in 2010-2012 which was taken from Iindonesia Stock Exchange branch Pontianak and also from several websites (http://www.idx.co.id/, http://finance.yahoo.com/). The result shows that the profitability and the leverage of the registered Manufacturing companies in Indonesia Stock Exchange  is categorised as poor and good respectively. The result from (uji t) shows that the profitability  has significant effect partially on stock prices, while the leverage does not, and the result from (uji F) shows that the financial performance (profitability and leverage) has significant effect on stock prices of the registered Manufacturing companies in Indonesia Stock Exchange simultaneously. Its effect on stock prices is arround 17.7%.  Keywords: Financial Performance, Stock Prices, Manufacturing Companies.